The Effect of HR Competence, Utilization of IT, and Internal Control Systems on the Financial Report Quality - Kasna Ningsih Kusuma; Mursalim Nohong; Andi Aswan (Hasanuddin Journal of Business Strategy, 2021)
The purpose of this study was to analyze the influence of human resource competence, the use of information technology, and internal control systems on the financial report quality of Jala Ammari Hospital in Makassar City. The study applied saturated samples of 95 hospital employees. Data collection methods using questionnaires and then analyzed using multiple linear regression. The results showed utilization of information technology and internal control system affect positively and significantly financial report quality. Interestingly, human resource competence had no significant effect on the financial report quality of the Jala Ammari Hospital Makassar.